2021
DOI: 10.1590/0001-3765202120190274
|View full text |Cite
|
Sign up to set email alerts
|

Yeast as growth promoter in two breeds of growing rabbits with special reference to its economic implications

Abstract: The present study investigated the effects of dietary supplementation of Saccharomyces cerevisiae (SC) on growth performance, carcass traits, blood biochemical parameters, histological changes in intestinal wall and economic indices in two breeds of weanling rabbits (V-Line and Rex). One-hundred and twenty weaned male rabbits were allotted randomly into four groups in factorial arrangement. The results could be summarized as follows: dietary supplementation of SC signifi cantly accelerated body weight gain (BW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…Regarding carcass characteristics, our findings were consistent with those observed by Abd El-Aziz et al [ 1 ], Mahrose et al [ 6 ], and Abo Ghanima et al [ 2 ]. Similarly, Mousa et al [ 11 ] showed that dressing and giblet percentages were significantly higher in the carcasses of rabbits that drank water supplemented with 1 mL Inmunair17.5 ® /litter.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding carcass characteristics, our findings were consistent with those observed by Abd El-Aziz et al [ 1 ], Mahrose et al [ 6 ], and Abo Ghanima et al [ 2 ]. Similarly, Mousa et al [ 11 ] showed that dressing and giblet percentages were significantly higher in the carcasses of rabbits that drank water supplemented with 1 mL Inmunair17.5 ® /litter.…”
Section: Discussionsupporting
confidence: 92%
“…The beneficial effects of adding FOS to the drinking water of growing rabbits may be due to the augmentation of feed efficiency and absorption, which improves anabolic metabolism, enhances the intestinal response to pathogens, and increases serum protein levels, thereby encouraging rabbit growth [ 1 , 6 , 7 ]. Prebiotics provide suitable environments for the growth of helpful microflora and inhibit the growth of pathogenic bacteria, which may explain the improvement in growth performance [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations